Application of Discussion Method to Improve Students’ PAI Learning Outcomes in SDN 05 Tonang Raya - Lina Mardiana (BiCED Proceeding, 2024)
This study aims to examine the effectiveness of using the discussion method in Islamic Religious Education and Moral Education in class IV at SDN 05 Tonang Raya. The research was conducted in two cycles using the Classroom Action Research (CAR) approach. The results showed that in Cycle I, the completion rate of student learning reached only 42%, while in Cycle II, it increased to 50%. Although there was an improvement, the results did not meet the expected target. Factors affecting learning outcomes include differences in students' abilities to participate in discussions and inefficient time management. This study suggests that improvements in class management and the use of more varied strategies are necessary to increase student engagement.